Effect of Feeding Moringa oleifera Leaf Powder on the Growth and Performance of Osmanabadi Kids (Indian Journal of Animal Production and Management, 2024)
The study was conducted at Goat Research  Project, Vasantrao Naik Marathwada Agricultural  University, Parbhani. Eighteen Osmanabadi kids  were selected and were allocated to three  experimental groups based on concentrate feed  replacement with Moringa oleifera Leaf Powder  (MOLP) i.e., T0 (0%), T1(10%) and T2 (20%). The  study lasted for 90 days in intensive rearing system.  The averages for weekly body weight (Kg) of kids  fed with MOLP for group T0, T1 and T2 at the end  of 13th week were 14.40±0.36, 14.86±0.47 and  16.40±0.45 kg, respectively depicting significantly  higher values for T2 group than Ti group whereas  non-significant difference between T0 and T1  group. The weekly body weight gain was 0.39±0.01,  0.40±0.01 and 0.54± 0.01 kg, respectively while the  daily weight gain observed were 55.95±2.07,  56.90±1.31 and 76.64±1.67 gm respectively with  highly significant difference between T2 group as  compared to T1 and T0 group. The mean values for  weekly and daily feed intake for groups T0, T1 and  T2 were 70.95±0.43 and 10.14±0.06, 71.38±0.41  and 10.20±0.06, and 70.40±0.06, and 10.06±0.01  kg, respectively. The feed conversion efficiency  (FCR) was significantly (P
Keywords: Osmanabadi kids; Moringa Oleifera leaf powder; body weight; feed and water intake; FCR